Crystal structure of 2,2-dichloro-1-(4-chloro-1H-indol-1-yl)ethan-1-one, C10H6Cl3NO - Ma Zhao-Yu; Lu Wan; Guo Yu-Chao; Li Ying-Jiao (Zeitschrift für Kristallographie - New Crystal Structures)
C10H6Cl3NO, monoclinic, P21/n (no. 14), a = 9.7097(10) Å, b = 10.6037(11) Å, c = 10.1735(10) Å, β = 96.580(4)°, V = 1040.55(18) Å3, Z = 4, Rgt(F) = 0.0214, wRref(F2) = 0.0574, T = 101 K.